Antifungal activity of wheat-flour sourdough (Type II) from two different Lactobacillus in vitro and bread - Ricardo H. Hernández-Figueroa; Emma Mani-López; Aurelio López-Malo (Applied Food Research, 2023)
This study aims to evaluate the antifungal capacity and chemical properties of the aqueous extracts (AE) obtained from the fermentation with Lactobacillus acidophilus NRRL B-4495 or L. casei 21/1 of wheat flour (poolish-type sourdough). The antifungal activity of poolish-type sourdoughs was tested against bread spoilage molds (Penicillium chrysogenum, and P. corylophilum) in vitro and bread. In addition, the physicochemical and sensory properties of bread formulated with the poolish-type sourdoughs were assessed. The AEs were obtained by separating the poolish supernatant at the end of fermentation (24, 48, or 72 h). Adding L. acidophilus or L. casei affects the sourdoughs’ pH and titratable acidity (TA), wherein the poolish added with L. casei presented a lower pH and higher acidity. HPLC identified mainly lactic acid in a concentration between 1 and 2% for the sourdoughs fermented with L. acidophilus, while for the poolish fermented by L. casei, lactic acid (1–2%) and acetic acid were identified (0.1–0.2%). Concentrations between 25 and 50% of AEs decreased the radial growth rate of P. crysogenum and P. corylophilum; in particular, the AEs obtained with L. acidophilus showed an effect on the growth of both molds. Bread added with sourdoughs fermented with Lactobacillus had an increase in shelf life compared to bread without them. There was an effect of the addition of poolish sourdoughs on the bread's physicochemical, quality, and sensory properties. But, incorporating L. acidophilus NRRL B-4495 or L. casei 21/1 into poolish-type sourdoughs can be an alternative as natural antifungal agents, useful for the bakery industry.